"Quale tristinita?" - Pizzi, Katia (Primerjalna književnost, 2005)
In focusing on Italian Trieste and, in particular, on as large as possible a corpus of Triestine poetry contemporary with Kosovel, my paper provides a perspective that is entirely peripheral and "exterior". Special attention is paid to the Futurist avant-garde: the Futurist leader Marinetti considered Trieste as Futurist city par excellence and the first Futurist soirees took place at Teatro Rossetti between 1909 and 1910. Futurism attracted a large group of local artists, some of whom (e.g. Carmelich and Cernigoj) were personally known by and became close to Kosovel, including the poets Sanzin and Miletti, who enthusiastically espoused Futurist linguistic experimentalism, as well as the movement's national/nationalist tendencies. Poetry of national and romantic inspiration is also of fundamental importance: Slataper's vitalist approach to the rugged Karst region, though pre-War, provides scope for comparative approaches. Nationalist poetry, much of which officially compromised with the Fascist regime (Cambon, Corraj, Alma Sperante), is equally integral to the Triestine cultural landscape of the 1920s and '30s. By shedding light on a significant portion of poetry in Italian arising from the vibrant, if largely hostile, cultural environment of Trieste, my paper invites an implicit rather than explicit assessment of Kosovel's role and contribution to the European avant-garde.
Keywords: Kosovel, Srečko, 1904-1926; Trst; slovenska poezija; italijanska poezija; tržaška književnost; literarna avantgarda; futurizem; literarni vplivi